2008
DOI: 10.1007/s10935-008-0157-5
|View full text |Cite
|
Sign up to set email alerts
|

Teens and the Misuse of Prescription Drugs: Evidence-Based Recommendations to Curb a Growing Societal Problem

Abstract: The misuse of prescription drugs by teens in the United States is a growing public health problem. This article provides a systematic synthesis of multiple strands of literature to recommend effective prevention methods. Using a social-ecological framework, we review the scope of the problem of prescription drug use among teens. Then, we analyze the multiple factors that may influence teen knowledge and attitudes toward prescription drugs and discuss the important challenges related to the construction of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…A multifaceted approach is necessary to improve parents' and adolescents' awareness about these and other risks of NMUPM [6]. For example, prescribing providers must take care to educate adolescent patients and caregivers about the risks of misuse and diversion of prescription drugs, and pharmacists should reiterate messages and monitor for abnormal prescription and refill patterns to assist in prevention.…”
Section: Implications For Treatment and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multifaceted approach is necessary to improve parents' and adolescents' awareness about these and other risks of NMUPM [6]. For example, prescribing providers must take care to educate adolescent patients and caregivers about the risks of misuse and diversion of prescription drugs, and pharmacists should reiterate messages and monitor for abnormal prescription and refill patterns to assist in prevention.…”
Section: Implications For Treatment and Preventionmentioning
confidence: 99%
“…Rather, the intent was to elucidate the social-ecological context of adolescent NMUPM. The review cited literature from governmental reports, popular media, as well as academic sources to demonstrate influences on adolescents' knowledge and attitudes about NMU of all prescription drugs [6].…”
mentioning
confidence: 99%
“…3 Youth have been identified at particularly high risk of harm when using these substances, and existing research has shown that youth view prescription drugs as "safer" than illegal drugs. 25 Of concern in our study is that, although only 6% of presentations were related to prescription drug use, this group had the highest admission rate (38% v. an average admission rate of 6.1% for single-drug ingestions).…”
Section: Discussionmentioning
confidence: 64%
“…Emerging research has indicated that one of the principal factors connected to increased NMUPD among youth and young adults is increased access to these drugs (McCabe, Cranford, Boyd & Teter, 2007). This has been in part attributed to less than conservative prescribing practices of doctors of opioid painkillers and changing medical guidelines (Twombly & Holtz, 2008). However, this also underscores the critical role that physicians can play in screening for and communicating about the negative effects of nonmedical use of prescription drugs with their patients.…”
Section: Discussionmentioning
confidence: 99%